Repurposing phenothiazines for cancer therapy: compromising membrane integrity in cancer cells - Mehrabi, Syrina Fred; Elmi, Sabina; Nylandsted, Jesper (Frontiers in Oncology, 2023)
The limitations of current cancer therapies, including the increasing prevalence of multidrug resistance, underscore the urgency for more effective treatments. One promising avenue lies in the repurposing of existing drugs. This review explores the impact of phenothiazines, primarily used as antipsychotic agents, on key mechanisms driving tumor growth and metastasis. The cationic and amphiphilic nature of phenothiazines allows interaction with the lipid bilayer of cellular membranes, resulting in alterations in lipid composition, modulation of calcium channels, fluidity, thinning, and integrity of the plasma membrane. This is especially significant in the setting of increased metabolic activity, a higher proliferative rate, and the invasiveness of cancer cells, which often rely on plasma membrane repair. Therefore, properties of phenothiazines such as compromising plasma membrane integrity and repair, disturbing calcium regulation, inducing cytosolic K-RAS accumulation, and sphingomyelin accumulation in the plasma membrane might counteract multidrug resistance by sensitizing cancer cells to membrane damage and chemotherapy. This review outlines a comprehensive overview of the mechanisms driving the anticancer activities of phenothiazines derivates such as trifluoperazine, prochlorperazine, chlorpromazine, promethazine, thioridazine, and fluphenazine. The repurposing potential of phenothiazines paves the way for novel approaches to improve future cancer treatment.